Statistical optimization of process parameters for removal of dyes from wastewater on chitosan cenospheres nanocomposite using response surface methodology. (15th April 2017) - Markandeya,; Dhiman, N.; Shukla, S.P.; Kisku, G.C.
Abstract: In the present study, an efficient, economical and effective wastewater treatment process based on response surface methodology for the removal of dyes using cenospheres, a waste product, in the form of nanocomposite with chitosan has been described. Chitosan cenospheres (10:3) nanocomposite was synthesized using glutaraldehyde, a crosslinking agent, precipitated in alkaline solution to adsorb Disperse Orange 25 (DO) and Disperse Blue 79:1 (DB) dyes. The synthesized nanocomposite was characterized using spectroscopic ATR-FTIR, microscopic SEM, particle size distribution DLS/CILAS and surface area BET techniques. Furthermore, Box–Behnken design was used to optimize operating variables namely: contact time (20–160 min for DO and 60 to 180 min for DB), pH (2–10), agitation speed (100–300 rpm), adsorbent dose (0.05–0.35 g/L) and adsorbate concentration (10–70 mg/L). Maximum percentage removal of dyes was found to be 97.30% and 94.22% for DO and DB respectively. Regression analysis and analysis of variance was performed to see the adsorption effect of dye molecules on the surface of nanocomposite. Synthesized chitosan cenospheres nanocomposite provided a feasible strategy to wastewater treatment. Graphical abstract: Schematic illustration of dye adsorption on CHCN nanocomposite. Highlights: Exploring the way of waste management in the form of nanocomposite by modifying coal fly ash. Confirming adsorbent fabrication by using modern instruments like ATR-FTIR, SEM, DLS/CILAS and BET. Dye removal from synthetic wastewater onto the surface of chitosan cenospheres nanocomposite used as an adsorbent. Demonstrating effect of multiple parameters on the remediation process using response surface methodology.